2020
DOI: 10.1161/jaha.120.016041
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Potential of Targeting Fibroblast Growth Factor‐23 and αKlotho in the Treatment of Uremic Cardiomyopathy

Abstract: Chronic kidney disease is highly prevalent, affecting 10% to 15% of the adult population worldwide and is associated with increased cardiovascular morbidity and mortality. As chronic kidney disease worsens, a unique cardiovascular phenotype develops characterized by heart muscle disease, increased arterial stiffness, atherosclerosis, and hypertension. Cardiovascular risk is multifaceted, but most cardiovascular deaths in patients with advanced chronic kidney disease are caused by heart failure and sudden cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 198 publications
0
16
0
2
Order By: Relevance
“…MR was not associated with myocardial α-Klotho mRNA expression. A decrease in renal and circulating α-Klotho is typical for hypertension and CKD [ 34 , 38 , 39 , 40 ], including the models used here. Thus, a decline in α-Klotho kidney production and circulating α-Klotho may be an additional factor in the progression of MR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR was not associated with myocardial α-Klotho mRNA expression. A decrease in renal and circulating α-Klotho is typical for hypertension and CKD [ 34 , 38 , 39 , 40 ], including the models used here. Thus, a decline in α-Klotho kidney production and circulating α-Klotho may be an additional factor in the progression of MR.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of MR in CKD are poorly understood and may include hemodynamic and non-hemodynamic factors [ 26 , 27 , 28 , 29 , 30 , 31 ]. The increased production of fibroblast growth factor-23 [ 32 , 33 ], αKlotho [ 34 , 35 ], and calcitriol [ 36 ] deficiencies are major candidate non-hemodynamic factors of cardiomyopathy progression in patients with CKD [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, we found that FGF-23 protein expression in heart tissue in CKD mice was similar to that in sham mice, suggesting that the high circulatory FGF-23 in CKD does not cause accumulation of FGF-23 in the heart. FGF-23 activates promoting cardiac hypertrophy gene transcription by binding to FGF receptors (FGFRs) on the surface of cardiomyocytes membrane, instead of directly entering the cells ( 41 ). Therefore, the function and activity of the FGFRs may be more important.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism has been suggested to be independent from alpha-Klotho, which is a co-receptor for FGF23-mediated regulation of mineral metabolism [ 33 ]. The failing heart can also be a major source of circulating FGF23, and patients who experience recurrent AF 6 months after AF ablation were observed to have greater left atrial FGF23 levels and lower soluble Klotho than patients with normal renal function [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%